A Novel Hydrogen Peroxide Sensor Based on Silver Nanoparticles Electrodeposited on PFS-DNA Networks Modified Glassy Carbon Electrode - He, Z.F.; Song, Y.H.; Wang, L.; Wan, L.L.; Zhu, H.Z.; Gao, S. (Asian Journal of Chemistry, 2012)
A novel hydrogen peroxide (H2O2) sensor based on the silver nanoparticles (Ag NPs) electrodeposited on a poly(ferrocenylsilane) (PFS)-DNA networks modified glassy carbon electrode (GCE) was successfully constructed. The electrochemical experiments showed that this Ag NPs/PFS-DNA/ GCE had a good catalytic ability toward the reduction of H2O2. The effects of PFS-DNA layers, electrodeposition time for silver nanoparticles formation and the pH of the electrolyte solution on the electrocatalytic reduction of H2O2 were investigated. Under the optimal conditions, the sensor exhibited a linear range of 2.0 μM to 35.3 mM with the detection limit of 0.6 μM. A rapid response of the sensor could achieve 95 % of the steady-state current in less than 2 s. This sensor with a high selectivity and sensitivity was expected to use for practical applications in detecting H2O2.